Angio-Arquitectura Visceral en 3D mediante Técnica de Plastinación por Corrosión: Visceral angio-arquitecture in 3D throught corrosion plastination technique (La U Investiga, 2017)
The preservation of anatomical structures arises from the embalming and mummification of corpses carriedout by the Egyptian civilization in the past ages until the development of the most modern techniques, which allow learning in anatomy and embryology ciences. Now at qdays plastination by corrosion injection technique allows reproducing the tubular structures in the visors. The aim of the study was the identificationof the visceral architecture in 3D using the technique of plastination by corrosion. For the plastination, freshvisors were selected; pig’s kidneys and lungs and a human placenta, which ones were injected with the polipoxic preparation colored with acrylics until get a expositation of the vascular tree, renal excretory structures and the trachebronquial tree. The results obtained facilitate the process of anatomy’s teachingto establish an analysment of the macroscopic details and the topographic relationship of the structures that comform the anatomical pieces.
Keywords: Plastination Technique; corrosion; epoxy resin